SEJARAH CHIKUNGUNYA DI INDONESIA, SUATU PENYAKIT RE EMERGING? - Wibowo, Wibowo (Media Penelitian dan Pengembangan Kesehatan, 2010)
Chikungunya also known as knuckle fever or joint fever, caused by Alphavirus infections. It was first time reported by laboratory test in Indonesia during Chikungunya outbreaks in Jambi and Yogyakarta provinces during 1982-1985. Epidemiology analysis indicated that during 1982-85 Chikungunya epidemic was occurred in 15 provinces, among young and adults. The symptoms were: fever 2-7 days onset of illness: 100%, joint fever: 95%; exanthema: 65% and headache: 100%. Serological test by HAI showed that 96/139% were Chikungunya positive. To 2001-2002 Chikungunya epidemic it was repEorted several chkungunya epidemics occurred in Sumatera and Java islands, 80/238% was serologically positive against IgM and IgG Chikungunya, 25/238% by Chik RT-PCR and there is no significantly different between diseases symptoms. It was also reported that A aegypti is a vektor dominant of the disease.   Keywords: Chikungunya, fever